FLOW PROCESS PRODUKSI KABEL HIGH VOLTAGE 150 KV (UGC) UNDERGROUND CABLE BERDASARKAN TATA LETAK FASILITAS DI PT BICC BERCA CABLES - Hakiki, Muhamad Rafi; Hermawan, Erwin; Putri, Monika; Budiharjo, Budiharjo (LPPM Universitas Bina Bangsa, 2024)
PT BICC Berca Cables is a company engaged in cable manufacturing that has been established since 1995. The cable products produced are of various types, namely, (1) low voltage cables, (2) medium voltage cables, high voltage cables, and (3) fiber optic cables. The types of cables are differentiated based on the size of the cable diameter, the mixture of raw materials used, and the use of the function of the cable. Various types of products require different raw materials, including variations in type and quantity. This study aims to analyze the production layout system to improve production efficiency and quality and reduce work accidents. The problem with the layout of existing facilities at PT. BICC Berca Cables is that there is a delay in supplying raw materials from machine A to machine B because of the long distance. Determining an efficient and effective machine facility layout can minimize waste during the production process